Novel Potential Feed Probiotics for Fish: Lactobacillus rhamnosus Vahe - Pepoyan, A. Z.; Manvelyan, A. M.; Balayan, M. H.; Mamikonyan, V. Kh. (ՀԱԱՀ հիմնադրամ)
The article considers the possible role of lactobacilli probiotics in protection of salmon against fish pathogens. The aim of this work is to study the viability of the potential probiotic Lactobacillus rhamnosus Vahe immobilized in salmon feed. Lactobacilli strains of human origin might have good probiotic efficacy in animals, including fish. According to this study, a decrease in viability (from 100 % to 78.00 ± 3.14 %) of the probiotic in feed biofilms was detected over a 2-month period. A simple procedure has been recommended that ensures viability of probiotics and can be applied for the evaluation of probiotic candidates in the future.
Keywords: Veterinary Science and Animal Breeding